Usefulness of High-Frequency Ultrasonography in the Diagnosis of Melanoma: Mini Review - Belfiore, Maria Paola; Reginelli, Alfonso; Russo, Anna; Russo, Gaetano Maria; Rocco, Maria Paola; Moscarella, Elvira; Ferrante, Marilina; Sica, Antonello; Grassi, Roberto; Cappabianca, Salvatore (Frontiers in Oncology, 2021)
High-frequency equipment is characterized by ultrasound probes with frequencies of over 10 MHz. At higher frequencies, the wavelength decreases, which determines a lower penetration of the ultrasound beam so as to offer a better evaluation of the surface structures. This explains the growing interest in ultrasound in dermatology. This review examines the state of the art of high-frequency ultrasound (HFUS) in the assessment of skin cancer to ensure the high clinical approach and provide the best standard of evidence on which to base clinical and policy decisions.